Diabetes Handlers by the DKI Jakarta Government - Etha Pasan; Tanika Oktavia (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to describe how the Diabetes Handling Efforts by the DKI Jakarta Government in 2018-2021. The type of research used is descriptive. The data used are the types of primary and secondary data obtained by the author through the results of internet access which contains relevant data and information related to the research discussed by the author. The results of the study showed that diabetes management by the DKI Jakarta Government was carried out internally and externally. Internally by forming POSBINDU PTM and GERMAS, and Externally Through Cooperation with Denmark.